The Police Authority in Granting Crowd Permit in The Makassar Port Police Area - Ammar Athief; Aspan, Zulkifli; Yunus, Ahsan; Nur Annisa, Arini (Sekolah Tinggi Ilmu Kepolisian, 2024)
Makassar City as the largest city in Eastern Indonesia is known to have a high crime rate. On the other hand, the most common and often faced community dynamics in Makassar city is community mobility that triggers crowds. So as a preventive effort, the police have the authority to issue a crowd permit to regulate community activities. This research aims to analyze the regulations and mechanisms for granting crowd permits and to identify the methods of police supervision of crowd activities in the Makassar Port Police area. The type of research used is empirical juridical research. Data collection is done through interviews and observations. The technique of analyzing research data starts from data reduction, data presentation, to verification and conclusion drawing. The results showed that: (1) Regulations in granting crowd permits are regulated in Law of the Republic of Indonesia Number 2 of 2002 concerning the Indonesian National Police and several Field Guidelines of the National Police Chief. The mechanism for granting permits includes: First, the criteria for activities are given for activities with large masses. Second, the flow of services has been listed in the task guidelines with clear steps. (2) Supervision of crowd activities is carried out through open maintenance of public security and order by the Samapta Bhayangkara (Sabhara) unit and closed by the Intelligence and Security Unit and the Criminal Investigation Unit. Meanwhile, supervision of police members is carried out through control by police administrative staff, discipline enforcement by the Profession and Security Unit, and post-activity and periodic consolidation and evaluation once a year. Thus, the authority of the Police in granting crowd permits in the Makassar Port Police area has been running well, although there are still shortcomings in terms of supervision, especially time security and police availability to accompany crowd activities until completion.